A Judge's Response to the Phenomenon of Indonesian Legal Pluralism: The Compartmentalization of Law on Divorce Case of Sasaknese Marriage - Murdan Murdan (Justicia Islamica, 2025)
The legal plurality in a civil and plural society, such as Indonesian, is necessary. Today, Indonesians practice state law and are subject to religious and customary law. The Sasaknese live in Indonesia's state territory, which requires them to submit to Indonesian state law. In contexts of ethnicity and local civilization, they need the pursuance of Sasak customary law, and in the context of Muslims, they need the subservience of Islamic law. These three laws have rules regarding marriage law, tradition, and culture. This article will discuss and deal with the response of the state officer and the Praya Religious Court in Lombok Island in the case of Sasaknese divorce. The approach is socio-legal studies and the theory of legal compartmentalization. A methodological study of this article deals with juridical-normative-empirical analysis. The critical point explored in this article is the attitude of legal compartmentalization as an essential response from judges in seeing the phenomenon of legal plurality in the Sasak society. The judges adopted legal compartmentalization to provide justice, and protection, and balance rights and obligations between men/husbands and women/wives in a family.